Aflatoxin production by Aspergillus flavus in rumen liquor and its implications. (January 2017) - Nidhina, N.; Bhavya, M.L.; Bhaskar, N.; Muthukumar, S.P.; Murthy, Pushpa S.
Abstract: Cow milk in infant and human nutrition is very significant. However, contamination of milk with aflatoxins is considered as a potential risk for human health. Aflatoxin is one of the major etiological factors in the development of hepatocellular carcinoma and is also found in the milk of lactating animals which could have consumed it through contaminated feedstuffs. Thus, exploration to isolate and identify the pathogenic microbe present in the rumen liquor were carried out. The screened fungal organism was identified as Aspergillus flavus by phenotypic (morphology and extrolite profiles) and molecular ( β -tubulin gene sequences) characters. Fungal toxin was extracted using immuno-affinity column (IAC) and quantified by High Performance Liquid Chromatography (HPLC). The organism had potential to grow under aerobic and anaerobic conditions and also produce aflatoxin B1. The aflatoxin B1 production under aerobic condition was 0.902 ± 0.08 μg/ml culture broth and anaerobic condition was 0.925 ± 0.2 μg/ml culture broth. Aflatoxin B2 was more compared to aflatoxin B1 and the quantity was 14.472 ± 1 under aerobic condition and 1.467 ± 0.3 under anaerobic condition. The rumen liquor from which the isolation was carried out also showed the presence of aflatoxin B1 (3.964 ± 0.5 μg/ml) and B2 (1.170 ± 0.6 μg/ml). However, aflatoxin G1 and G2 were not present. Hence, the study suggests the ability of microbial ecosystem present inside the rumen to produce aflatoxin. This report on the aflatoxin production under aerobic and anaerobic conditions provides insights about the possibility of aflatoxin in cow milk thereby effecting human health. It is vital to reduce exposure of milking animals to contaminated moldy feed and take precautions to prevent fungal contaminations in the feed. Highlights: Aflatoxin B1 and B2 producing Aspergillus flavus was isolated from rumen liquor. Rumen liquor from which the isolate was obtained, contained aflatoxin B1 and B2 . Microbial inhabitants of rumen also can be a source of aflatoxin in rumen. Aflatoxin B1 may be converted to aflatoxin M1 and excreted into cow milk. This is the first report anaerobic production of aflatoxin B1 and B2 .